2016
DOI: 10.1039/c6ta02059c
|View full text |Cite
|
Sign up to set email alerts
|

Facile formation of a nanostructured NiP2@C material for advanced lithium-ion battery anode using adsorption property of metal–organic framework

Abstract: Utilizing the adsorption properties of MOFs, a nanostructured NiP2@C was successfully synthesized, which exhibited enhanced capability for lithium storage in terms of both the reversible specific capacity and high-rate performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
72
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 43 publications
5
72
0
Order By: Relevance
“…The trend between the level of phosphidation and specific capacity can be attributed to the electrochemical reaction mechanism between Li + ions and nickel phosphide, which involves intercalation and conversion. During discharge, it has been proposed that lithium ions first intercalate with Ni x P y to form LiNi x P y complexes, followed by conversion to Li 3 P and Ni metal . Nickel phosphides with higher phosphorus content will yield stoichiometrically more Li 3 P during discharge and therefore have intrinsically higher theoretical capacities.…”
Section: Resultsmentioning
confidence: 99%
“…The trend between the level of phosphidation and specific capacity can be attributed to the electrochemical reaction mechanism between Li + ions and nickel phosphide, which involves intercalation and conversion. During discharge, it has been proposed that lithium ions first intercalate with Ni x P y to form LiNi x P y complexes, followed by conversion to Li 3 P and Ni metal . Nickel phosphides with higher phosphorus content will yield stoichiometrically more Li 3 P during discharge and therefore have intrinsically higher theoretical capacities.…”
Section: Resultsmentioning
confidence: 99%
“…The high diffusion coefficient explains the excellent rate performance and long‐cycle stability of M‐FeP@C hybrid nanofibers. Figure g shows a comparison of rate performance of M‐FeP@C and other phosphide‐based anodes ,,. It can be clearly observed that the 1D M‐FeP@C hybrid nanofibers have superior rate performance.…”
Section: Resultsmentioning
confidence: 99%
“…The G band is the result of a radial C-C stretching mode of sp 2 -bonded carbon, and the G bond is from a rst-order zone boundary phonon mode associated with defects in the graphene or graphene edge. 20,41,46 Because the height of the G band is higher than that of D band, this carbon material is of low defect density, which is benecial for electron transfer. Raman peak for initial SnO 2 nanoparticles and SOC-3 were also tested to identify structural change (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, by carbonizing Ni-based metal-organic framework (Ni-MOF-74) with adsorptive red phosphorus precursors, NiP 2 @C nanocomposites were successfully synthesized and exhibited excellent reversible capacity of 656 mA h g À1 at 50 mA g À1 aer 50 cycles. 41 SnO 2 @C nanocomposite exhibiting a high reversible capacity of 900 mA h g À1 at 100 mA g À1 aer 50…”
Section: Introductionmentioning
confidence: 99%